Anaerobic oxidation of methane in paddy soil: Role of electron acceptors and fertilization in mitigating CH4 fluxes. (February 2020) - Fan, Lichao; Dippold, Michaela A.; Ge, Tida; Wu, Jinshui; Thiel, Volker; Kuzyakov, Yakov; Dorodnikov, Maxim
Abstract: The anaerobic oxidation of methane (AOM) in marine ecosystems is ubiquitous and largely coupled to sulfate reduction. In contrast, the role of AOM in terrestrial environments and the dominant electron acceptors driving terrestrial AOM needs deeper understanding. Submerged rice paddies with intensive CH4 production have a high potential for AOM, which can be important for greenhouse gas mitigation strategies. Here, we used 13 CH4 to quantify the AOM rates in paddy soils under organic (Pig manure, Biochar) and mineral (NPK) fertilization. Alternative-to-oxygen electron acceptors for CH4 oxidation, including Fe 3+, NO3 −, SO4 2−, and humic acids, were examined and their potential for CH4 mitigation from rice paddies was assessed by 13 CH4 oxidation to 13 CO2 under anoxic conditions. During 84 days of anaerobic incubation, the cumulative AOM (13CH4-derived CO2) reached 0.15–1.3 μg C g-1 dry soil depending on fertilization. NO3- was the most effective electron acceptor, yielding an AOM rate of 0.80 ng C g-1 dry soil h-1 under Pig manure. The role of Fe3+ in AOM remained unclear, whereas SO42- inhibited AOM but strongly stimulated the production of unlabeled CO2, indicating intensive sulfate-induced decomposition of organic matter. Humic acids were the second most effective electron acceptor for AOM, but increased methanogenesis by 5–6 times in all fertilization treatments. We demonstrated for the first time that organic electron acceptors (humic acids) are among the key AOM drivers and are crucial in paddy soils. The most pronounced AOM in paddy soils occurred under Pig manure, followed by Control and NPK, while AOM was the lowest under Biochar. We estimate that nitrate (nitrite)-dependent AOM in paddy fields globally consumes 3.9 Tg C–CH4 yr-1, thereby offsetting the global CH4 emissions by 10–20%. Thus, from a broader agroecological perspective, the organic and mineral fertilizers control an important CH4 sink under anaerobic conditions in submerged ecosystems. Appropriate adjustments of soil fertilization management strategies would therefore help to decrease the net CH4 flux to the atmosphere and hence the global warming. Graphical abstract: Image 1 Highlights: Anaerobic oxidation of methane (AOM) was measured in paddy soils using 13 CH4 . Electron acceptors efficiency for AOM revealed pattern NO3 − > Humic acids > Fe 3+ >SO4 2- . The highest AOM rate was 0.8 ng C g −1 dry soil h −1 under Pig manure fertilization. The lowest AOM potential was under NPK and Biochar field fertilization treatments. Nitrate induced AOM may recycle 3.9 Tg C–CH4 per year in paddy fields globally.